Pengembangan Sistem Informasi Geografis Wisata Berbasis Web Di Kabupaten Majalengka Menggunakan Metode RAD (Studi Kasus: Dinas Pariwisata Dan Kebudayaan) - Kartadilaga, Septian Nugraha; Sopiandi , Ii (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Tourism is a crucial sector for increasing regional income while promoting local potential. Majalengka Regency boasts a variety of tourist destinations, both natural and man-made, yet promotion and information provision remain limited. This study aims to design and implement a web-based Tourism Geographic Information System (GIS) that can provide comprehensive information on tourist destinations in Majalengka Regency. The system development method used is Rapid Application Development (RAD) with the stages of requirements planning, system design, development, and testing. The system was built using modern web technology, making it easily accessible without additional installation. Test results using the black-box testing method indicate that the system is capable of displaying destination information interactively, including descriptions, facilities, ticket prices, map locations, reviews, and ratings. For administrators, the system facilitates fast and efficient management of tourism data. Thus, the implementation of a web-based tourism GIS using the RAD method increases the effectiveness of tourism promotion and supports destination management in Majalengka Regency.